2011
DOI: 10.1097/iae.0b013e318203c1ef
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Spectral-Domain Optical Coherence Tomography Findings of Multifocal Choroiditis

Abstract: The acute lesions of MFC can be difficult to distinguish from myopic CNV based on clinical examination and fluorescein angiography. However, the inflammatory lesions of MFC can demonstrate characteristic SD-OCT findings not seen with myopic CNV. These SD-OCT findings may help to differentiate these two entities that typically require different treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 11 publications
0
47
1
1
Order By: Relevance
“…10 In our case, there was both RPE and choroidal hyperreflectivity. One theory regarding the formation of such streaks is that the underlying inflammatory process can lead to tangential stress with subsequent mechanical disruption of the RPE.…”
Section: Discussionmentioning
confidence: 90%
“…10 In our case, there was both RPE and choroidal hyperreflectivity. One theory regarding the formation of such streaks is that the underlying inflammatory process can lead to tangential stress with subsequent mechanical disruption of the RPE.…”
Section: Discussionmentioning
confidence: 90%
“…1 In neovascular age-related macular degeneration and myopic CNV, Type 2 neovascularization has a characteristic OCT appearance as an additional linear hyperreflective line above the RPE band. 10 Olsen et al 11 showed that, in terms of histopathology and ultrastructure, the features of subfoveal CNV surgically excised from 6 eyes of 5 patients with PIC could be classified as Type 2 neovascularization. This report proposed five stages in the evolution of the bridging CNV associated with PIC, starting from the initial inflammatory reaction at the choriocapillaris or RPE resulting in a focal injury to the Bruch membrane (Stage 1) allowing small neovascular buds/foci to grow through the Bruch membrane toward the subretinal space (Stage 2) that then bridge and coalesce to form a single larger subretinal CNV (Stage 3).…”
Section: Discussionmentioning
confidence: 98%
“…13 A previous report from our group compared the OCT findings of MFC and myopic degeneration. 10 Specifically, Cases 2 and 4 are likely inflammatory CNV due to the absence of characteristic features of myopic CNV, which include the presence of a posterior staphyloma, a typical Type 2 CNV OCT pattern, and an extremely thin choroid. 10 Optical coherence tomography findings of the acute lesions of MFC showed presumed cells in the vitreous inflammatory material between the RPE and the Bruch membrane and localized choroidal hyperreflectivity below the subretinal pigment epithelial material that diminished after resolution of the acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…42 Optical coherence tomography of MFC shows hyperreflective material between the RPE and the Bruch membrane corresponding to lesions observed clinically and choroidal hyperreflectivity below these lesions. 42,43 These findings confirm those previously observed on fluorescein angiography, specifically the early hypofluorescence of the lesions, which 44 Case studies also report disruption of the outer retinal layers (Fig. 3C) and sub-RPE deposits (Fig.…”
Section: Multiple Evanescent White Dot Syndromementioning
confidence: 98%